The bank of Japan's super-easy monetary policy from 2013-2018 - Sayuri Shirai (Asian Development Bank Institute (ADBI), 2018)
Unconventional monetary easing conducted by the Bank of Japan (BOJ) since 2013 has contributed to the yen's depreciation, higher stock prices, and higher corporate profits. Meanwhile, the impacts on aggregate demand and inflation have not been as strong as the BOJ expected while the adverse impact on financial institutions and deep distortion in the financial and capital markets have become prevalent. Therefore, the BOJ will eventually need to make it more sustainable before underlying inflation approaches 2%. Leaving room for additional monetary accommodation in the event of severe recession is also essential. Keeping the possible phasing out of the program in mind, the BOJ explicitly expanded the target range to ±0.2%, thereby effectively raising the yields of 10 years and longer and steepening the yield curve. At the same time, the BOJ introduced flexibility on exchange-traded fund (ETF) purchases that would enable "stealth tapering" or cutting the amount of annual purchase amount quietly without declaring it openly - as in the case of Japanese Government Bond (JGB) purchases. The BOJ should interpret the 2% price stability target flexibly - such as the incorporation of the 1% upper and lower range (±1%) to the 2% target - in order to complete tapering of both JGBs and ETFs, as well as ultimately eliminating the 10-year yield target. Since the Japanese economy is likely to face an economic slowdown after the 2019 consumption tax hike and the 2020 Tokyo Olympic Games, it will be much longer before the BOJ can take decisive steps to normalize monetary policy by raising the short-term policy rates like the Federal Reserve.
Keywords: E3; E4; E5; 330; Bank of Japan; Japanese Government Bonds; Exchange-Traded Funds; 2% Price Stability Target